Book Review: John Baxter, Charles Boyer: The French Lover. Issue 1 (4th July 2022) - Bell, Stuart
Abstract : JohnBaxter, Charles Boyer: The French Lover (Lexington: University Press of Kentucky, 2021), pp. vii-254, ISBN978-0813155524 (hb), $33.